Cultural Festivals in Borneo’s Tails: A Tourism Potential as City Branding in Sambas - sumar’in (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Sambas possesses significant potential for developing its natural resources into tourism assets, supporting local city branding initiatives. Efforts to promote Sambas as a tourist destination have included hosting culturally-rooted festivals, which stimulate the local economy by attracting visitors and creating business opportunities for residents. This study aims to assess Sambas Regency's tourism scope by identifying tourism areas in West Kalimantan, using a qualitative-descriptive approach. This approach focuses on the cultural festivals in Sambas Regency, which hold considerable tourism potential. The findings reveal that although various efforts have been made to promote Sambas, practical challenges persist. Visitor motivation can be enhanced by addressing factors such as festival cleanliness, food variety, beach conditions, and event program content. Despite these initiatives, most festival attendees are locals from West Kalimantan, with limited foreign tourist engagement. This study highlights both the progress and areas needing improvement in promoting Sambas as a unique cultural tourism destination.